Виділення щільних областей у метричних просторах на основі кристалізації - Agayan, S. M.; Soloviev, A. O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Application of artificial intelligence methods and fuzzy sets theory to the clusterization problem is considered. Data on dense accumulations in finite metric spaces is an object of the research. Calculations based on the fuzzy sets theory and “optical” approach to the metric space analysis are used. The result of the research is realization of “Crystal” algorithms in searching for dense areas in multidimensional data arrays.